2021
DOI: 10.3389/fcvm.2021.779073
|View full text |Cite
|
Sign up to set email alerts
|

Platelet Phenotype Analysis of COVID-19 Patients Reveals Progressive Changes in the Activation of Integrin αIIbβ3, F13A1, the SARS-CoV-2 Target EIF4A1 and Annexin A5

Abstract: Graphical Abstract

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
14
0
1

Year Published

2022
2022
2023
2023

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 21 publications
(17 citation statements)
references
References 73 publications
(84 reference statements)
2
14
0
1
Order By: Relevance
“…RNA sequencing of platelets in COVID-19 patients has revealed an altered transcriptional profile with enrichment in the pathways of antigen presentation, protein ubiquitination and mitochondrial dysfunction ( 12 ). Phenotypic analysis of platelets in COVID-19 demonstrated that platelets undergo a series of functional and biochemical changes most pronounced in patients with severe disease ( 20 ). In addition, SARS-CoV-2 has been shown to associate with ( 21 ) and bind ACE2 receptors on the platelet surface ( 22 ), whereas other studies have demonstrated that platelets can internalize SARS-CoV-2 virions in a process that contributes to their hyperactivated state ( 23 ).…”
Section: Introductionmentioning
confidence: 99%
“…RNA sequencing of platelets in COVID-19 patients has revealed an altered transcriptional profile with enrichment in the pathways of antigen presentation, protein ubiquitination and mitochondrial dysfunction ( 12 ). Phenotypic analysis of platelets in COVID-19 demonstrated that platelets undergo a series of functional and biochemical changes most pronounced in patients with severe disease ( 20 ). In addition, SARS-CoV-2 has been shown to associate with ( 21 ) and bind ACE2 receptors on the platelet surface ( 22 ), whereas other studies have demonstrated that platelets can internalize SARS-CoV-2 virions in a process that contributes to their hyperactivated state ( 23 ).…”
Section: Introductionmentioning
confidence: 99%
“…The protein αIIbβ3 is a heterodimeric platelet receptor that plays an essential role in platelet aggregation (Ma et al ., 2007). A previous study showed that the level of αIIbβ3 activation on platelets from non-surviving COVID-19 patients decreased compared to survivors (Ercan et al ., 2021, 5). The mechanism for the decline in αIIbβ3 in severe COVID-19 patients was unknown.…”
Section: Discussionmentioning
confidence: 99%
“…Dysregulation of this gene pathway may contribute to downstream effects of antigen presentation and sustained T cell activation [75]. Lastly, the 5 cap of SARS CoV-2 is recognized by Eukaryotic initiation factor 4A-1 (EIF4A1) [76] and is known to be significantly increased in the platelet proteome of COVID-19 patients thought to affect viral replication and downstream activation of platelets, resulting in thrombotic microangiopathy and increased mortality [77]. Collectively, the results of our WGCNA analysis identified a substantial network of dysregulated genes with many downstream effects that are linked to clinicopathologic data.…”
Section: Discussionmentioning
confidence: 99%